Selective isolation of rare actinomycetes from mangrove sediment of Tanjung Lumpur, Kuantan - Mohamad, Nur Hanisah; Zainal Abidin, Zaima Azira; Chowdhury, Ahmed Jalal Khan (2013)
Actinomycetes are renowned as a rich source of bioactive molecules. However, the commercially potent secondary metabolites from well-known actinomycetes are difficult to discover due to the practice of screening that is leading to rediscovery of known bioactive compounds, thereby, emphasizing the need to isolate undiscovered actinomycetes. Mangroves are highly productive ecosystem though less attention has been given into the diversity of actinomycetes present in mangrove sediment particularly in Malaysia. This study is aimed to isolate actinomycetes from sediment samples which were collected from mangrove in Tanjung Lumpur using several pretreatments and various selective media. Sediments from five different sites at Tanjung Lumpur mangrove were collected and pre-treated using several procedures including (i) wet heat in sterilized sea water (55oC, 15 min); (ii) dry heat (120oC, 60 min); and (iii) phenol (1.5%, 30oC, 30 min). The pretreated sediment samples were diluted and plated onto eight selective isolation media including, yeast-extract-malt-extract agar, oat-meal agar, inorganic salt starch agar, starch-yeast-extract agar, marine agar, actinomycetes isolation agar, Gause modified medium and starch-casein agar. All media were supplemented with 50 mg/l cycloheximide to inhibit fungal growth followed by incubation at 28-30oC for two weeks. A total of 172 potential actinomycetes were isolated. The highest numbers of isolates were obtained from sediment samples collected from Location 5. The sediment treated with sterilized sea water was the most effective method for the isolation of actinomycetes as it yielded maximum of 105 CFU of actinomycetes. Starch-casein agar was the most suitable medium as it showed the highest percentage for the recovery of actinomycetes (31 %). The dominance of other bacteria and fungal contamination can inhibit the colonization of actinomycetes. Therefore the use of various pretreatments and selective media helped to decrease the number of unwanted bacterial and fungal colonies. These findings proved the potential of mangrove sediment of Tanjung Lumpur possessed as an important source of rare actinomycetes. Keywords: actinomycetes, Tanjung Lumpur, mangrove sediment, pretreatments, selective media